Ex vivo aorta patch model for analysis of cellular adhesion. Issue 3 (June 2015) - Lin, Yuan-Na; Thata, Raymond Nqobizitha; Failla, Antonio Virgilio; Geissen, Markus; Daum, Guenter; Windhorst, Sabine
Highlights Here we present a new model to study cell–endothelium interaction onto an intact endothelial cell layer by plating HCT-116 cells onto mouse aortic patches. Validation of this model was performed by demonstrating changes in cell shape and development of cell protrusions typical for cell spreading. A major advantage of this model is that cell–endothelium interaction and its molecular backgrounds can now be studied more feasibly on an intact and native tissue.